2013
DOI: 10.1002/14651858.cd004253.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for women with metastatic breast cancer

Abstract: Psychological interventions appear to be effective in improving survival at 12 months but not at longer-term follow-up, and they are effective in reducing psychological symptoms only in some of the outcomes assessed in women with metastatic breast cancer. However, findings of the review should be interpreted with caution as there is a relative lack of data in this field, and the included trials had reporting or methodological weaknesses and were heterogeneous in terms of interventions and outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 106 publications
5
101
0
3
Order By: Relevance
“…[23] However, there is significant controversy around whether or not BPSI improves survival. [24] This has resulted from factors including lack of consistency in definition of intervention, [25] and inadequate sample sizes. Coyne et al report that trials in which "survival" was the "a priori" endpoint for psycho-therapeutic interventions have not shown to impact median survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] However, there is significant controversy around whether or not BPSI improves survival. [24] This has resulted from factors including lack of consistency in definition of intervention, [25] and inadequate sample sizes. Coyne et al report that trials in which "survival" was the "a priori" endpoint for psycho-therapeutic interventions have not shown to impact median survival.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Given the fact that there are over 3 million long-term breast cancer survivors in United States, focusing on "survival" may be the wrong approach. There is no doubt that cancer survivors in general [27][28][29][30] and breast cancer survivors in particular [24,31,32] face several issues pertaining to "quality" as opposed to "quantity" of life that could be positively impacted by psychosocial interventions. These issues include body-image concerns, difficulties in tolerating treatment side-effects, lack of compliance, social isolation, and lack of emotional support -all of which can directly hamper re-assimilation of survivors in society as productive members.…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight scientific reviews 40,[60][61][62][73][74][75][76][77] that reported the effects of psychoeducational interventions such as cognitive-behavioural techniques or education for bca patients and survivors, one 61 reported statistically significant benefits for fatigue (p < 0.001), depression (p < 0.001), anxiety (p < 0.001), and body image (p < 0.051). Two reviews found clinically important benefits for anxiety, depression, and stress levels with moderate-intensity activity 60,73 ; one reported benefits for mobility, muscle strength, and general fitness, and clinically important benefits for sexual functioning 62 ; four reported short-term benefits for overall survival with low-intensity activity, and also improvements in mood and pain reduction [74][75][76][77] ; and yet another reported significant reductions in fatigue, nausea, oral mucositis, diarrhea, constipation, pain, and insomnia, and improved qol 60 .…”
Section: Psychoeducational Interventionsmentioning
confidence: 99%
“…Two reviews found clinically important benefits for anxiety, depression, and stress levels with moderate-intensity activity 60,73 ; one reported benefits for mobility, muscle strength, and general fitness, and clinically important benefits for sexual functioning 62 ; four reported short-term benefits for overall survival with low-intensity activity, and also improvements in mood and pain reduction [74][75][76][77] ; and yet another reported significant reductions in fatigue, nausea, oral mucositis, diarrhea, constipation, pain, and insomnia, and improved qol 60 .…”
Section: Psychoeducational Interventionsmentioning
confidence: 99%
“…Women with metastatic breast cancer often are not included or included in such small numbers in those trials that reliable subgroup analyses are not possible. A recent review and meta-analysis of ten psychological RCTs with 1,378 women diagnosed with metastatic breast cancer included three trials of distinct individual approaches and seven group psychotherapy trials (four supportive-expressive therapy trials and three cognitive-behavioral trials) (Mustafa et al 2013 ). Although some trials produced psychological benefi t, the meta-analysis did not yield a clear pattern of psychological effects, given that a wide variety of outcome measures and follow-up durations were used.…”
Section: Care Of Women With Metastatic Diseasementioning
confidence: 99%